Nursing Case Study of Patients with Acute Gastroenteritis and Post-Syncope - Asri; Winata, Septian Galuh; Rofiqi, Erfan (Jurnal Keperawatan Muhammadiyah, 2023)
This case study probes the medical journey of Mrs. H, a 34-year-old female diagnosed with acute gastroenteritis and post-syncope. Her condition, marked by severe vomiting, dehydration, and repeated fainting spells, is thoroughly examined through an in-depth exploration of her presenting symptoms and medical history. This examination presents a comprehensive view of her health, considering potential diagnoses against her symptoms and medical history. Mrs. H’s medical history reveals a chronic struggle with Gastroesophageal Reflux Disease (GERD), which necessitated hospitalization on three occasions. The study also addresses nursing interventions implemented during her hospital stay, including hydration, symptom management, and patient education. The role of these interventions in her recovery is highlighted. The study concludes with a discussion on the discharge planning process, which ensures a smooth transition from the hospital to her home. These findings offer valuable insights into the management of acute gastroenteritis and post-syncope, highlighting the importance of comprehensive patient care that addresses both physical symptoms and psychological needs.